Effect of VP3 Biological Fertilizer Enriched with Trichoderma viride FRP3 on Growth and Chlorophyll Content in Soybean Leaves (Glycine max. L) - Wandi Wandi (AGRONISMA, 2022)
Biofertilizer is a living microorganism material that is useful for increasing soil fertility and the quality of a plant's production. VP3 biofertilizer is a liquid biofertilizer formulation made from vermiwash as a carrier, molasses, PEG, and 3 functional bacterial isolates. In this study, the VP3 biofertilizer will be enriched with Trichoderma viride FRP3. This study aims to determine the effect of giving VP3 biofertilizer enriched with Trichoderma viride FRP3 on yield and chlorophyll content in Soybean (Glycine max) leaves. This study was an experiment in polybags conducted at the Greenhouse using a Randomized Block Design consisting of 7 treatments, each treatment repeated 3 times and each replication using 4 plant samples. The variables observed included growth variables consisting of plant height, number of leaves and leaf area and leaf chlorophyll content. Data from observations on each plant parameter were then tested using analysis of variance F test with a level 5% significant, if there is a significant effect between treatments followed by Duncan's test at 5% level.The results showed that the application of VP3 biofertilizer enriched with Trichoderma viride FRP3 had no significant effect on plant growth parameters, because in general the treatment of N (m (using NPK fertilizer) showed high yields compared to other treatments, but the application of VP3 biological fertilizer enriched with Trichoderma viride FRP3 in the chlorophyll content of soybean leaves was able to compensate for the application of inorganic NPK fertilizer.